Variation in incidence, prevention and treatment of persistent air leak after lung cancer surgery. (19th August 2021) - Hoeijmakers, Fieke; Hartemink, Koen J; Verhagen, Ad F; Steup, Willem H; Marra, Elske; Röell, W F Boudewijn; Heineman, David J; Schreurs, Wilhelmina H; Tollenaar, Rob A E M; Wouters, Michel W J M
Abstract:  : OBJECTIVES: Persistent air leak (PAL; >5 days after surgery) is the most common complication after pulmonary resection and associated with prolonged hospital stay and increased morbidity. Literature is contradictory about the prevention and treatment of PAL. Variation is therefore hypothesized. The aim of this study is to understand the variation in the incidence, preventive management and treatment of PAL. METHODS: Data from the Dutch Lung Cancer Audit for Surgery were combined with results of an online survey among Dutch thoracic surgeons. The national incidence of PAL and case-mix corrected between-hospital variation were calculated in patients who underwent an oncological (bi)lobectomy or segmentectomy between January 2012 and December 2018. By multivariable logistic regression, factors associated with PAL were assessed. A survey was designed to assess variation in (preventive) management and analysed using descriptive statistics. Hospital-level associations between management strategies and PAL were assessed by univariable linear regression. RESULTS: Of 12 382 included patients, 9.0% had PAL, with a between-hospital range of 2.6–19.3%. Factors associated with PAL were male sex, poor lung function, low body mass index, high American Society of Anesthesiologists (ASA) score, pulmonary comorbidity, upper lobe resection, (bi)lobectomy (vs segmentectomy), right-sided tumour and robotic-assisted thoracic surgery. Perioperative (preventive) management of PAL differed widely between hospitals. When using water seal compared to suction drainage, the average incidence of PAL decreased 2.9%. CONCLUSIONS: In the Netherlands, incidence and perioperative (preventive) management of PAL vary widely. Using water seal instead of suction drainage and increasing awareness are potential measures to reduce this variation. Abstract : Persistent or prolonged air leak (PAL) is one of the most common complications after pulmonary resection, with incidence rates reported between 8% and 26% [1–8].